Role of Perindopril in Mitigating Doxorubicin’s Vascular Toxicity in a Rat Model - Anna Marada; Tibor Stračina; Filip Marhefka; Lucie Šůstková; Jaroslav Nádeníček; Jindra Smutná; Peter Scheer; Jana Hložková; Michal Hendrych; Christian Studenik; Hana Paulová; Marie Nováková (Cardiovascular Toxicology, 2026)
Doxorubicin (DOX), a widely used anthracycline in cancer therapy, is associated with significant cardiovascular toxicity. While its cardiotoxic effects are well documented, the mechanisms and prevention of DOX-induced vascular toxicity remain insufficiently explored. Angiotensin-converting enzyme inhibitors (ACEIs), such as perindopril (PER), are commonly used in cardiovascular disease management and may offer vascular protection during chemotherapy. Female ovariectomized Wistar rats were treated with i.v. DOX and/or p.o. PER over five weeks. Cardiac and vascular function were assessed using high-frequency ultrasound and ECG. Vascular reactivity was evaluated in isolated aortal rings using phenylephrine (PE), acetylcholine (ACh), L-N-Nitro arginine methyl ester hydrochloride (L-NAME), and verapamil (VER). Oxidative stress was assessed via plasma 4-hydroxy-2-nonenal (4-HNE) levels, and structural changes were monitored through intima-media thickness (IMT) measurements. DOX administration significantly impaired vascular reactivity, as evidenced by increased contractile responses to PE and reduced endothelium-dependent relaxation. These functional alterations were accompanied by elevated plasma 4-HNE levels, indicating enhanced oxidative stress. Co-treatment with PER preserved vascular responsiveness, reduced contractile tension, and significantly lowered 4-HNE concentrations. Structurally, IMT increased in control and PER-only groups, likely due to post-ovariectomy remodelling, while DOX-treated groups showed no IMT progression. PER co-treatment appeared to stabilize IMT values. PER mitigates DOX-induced vascular toxicity, likely through endothelial protection and reduction of oxidative stress. These findings support the potential use of ACEIs as prophylactic agents in patients undergoing anthracycline-based chemotherapy and highlight the need for further translational studies in cardio-oncology. Graphical Abstract

Impact of plastic rain shields and exclusion netting on pest dynamics and implications for pesticide use in apples - Robert Bischoff; Hans-Peter Piepho; Christian Scheer; Georg Petschenka (Journal of Plant Diseases and Protection, 2025)
Apple production is among the most pesticide-intensive cultures. Recently, plastic rain shields and pest exclusion netting have emerged as potential measures to reduce the heavy reliance on chemical pesticides in apple, due to their inhibitory effect on pathogen and pest infestations. In a field trial, we compared yields, pest, and pathogen abundance in an orchard consisting of four plots, where two plots were covered with anti-hail net covers, one with plastic rain shields only, and one with plastic rain shields and exclusion netting. Pests and pathogens were assessed visually, and beating tray samples were collected to compare overall arthropod diversity between plots. We observed virtually no scab infections in both plastic rain shield plots, despite a more than 70% reduction of fungicides applied, when compared to anti-hail plots. Although no codling moth insecticides were sprayed in the plot with exclusion netting we found significantly reduced damage here, when compared to the anti-hail plots. However, likely due to microclimatic changes, we observed an increase of powdery mildew, woolly apple aphids, and spider mites under plastic rain shields. Modeling of metabolic rates of arthropod herbivores and predators revealed that there is an increased potential of herbivory under plastic rain shields. However, in terms of plant protection, the net effect of plastic rain shields and exclusion netting was a substantial reduction in chemical pesticide use, demonstrating that they represent a promising approach to minimize the use of chemical pesticides in apple production.

Correction to: Denitrification in Agricultural Soils– Integrated control and Modelling at various scales (DASIM) - Kristina Kleineidam; Jürgen Böttcher; Klaus Butterbach‑Bahl; Michael Dannenmann; Klaus Dittert; Peter Dörsch; Sebastian Fiedler; Torsten Frosch; Balázs Grosz; Sina Henjes; Marcus A. Horn; Olaf Ippisch; et al. (Biology and Fertility of Soils, 2025)

Tube weaning in children with Down's syndrome—“Waiting is no option” - Karoline Pahsini; Sabine Marinschek; Elisabeth Beckenbach; Eva Z. Reininghaus; Nina Dalkner; Marion Russell; Asa N. Russell; Sophie Stoesslein; Peter J. Scheer; Marguerite Dunitz-Scheer (Appetite, 2025)

Denitrification in Agricultural Soils – Integrated control and Modelling at various scales (DASIM) - Kristina Kleineidam; Jürgen Böttcher; Klaus Butterbach-Bahl; Michael Dannenmann; Klaus Dittert; Peter Dörsch; Sebastian Fiedler; Torsten Frosch; Balázs Grosz; Sina Henjes; Marcus A. Horn; Olaf Ippisch; et al. (Biology and Fertility of Soils, 2025)
The special issue summarises and highlights key findings of the research unit DASIM funded by the German Research Foundation (DFG) on the process of denitrification. Progress was made in several areas including the development of new and advanced methods to quantify N 2 fluxes such as a new 15 N gas flux method, enhanced Raman spectroscopy and a new incubation system to study plant-soil interactions in He-O 2 atmosphere. Understanding of denitrification in disturbed and structured soil was gained by combining X-ray CT scanning and microbial ecology methods. High resolution models developed as part of DASIM were able to successfully simulate experimental data and provide valuable insights for the improvement of existing ecosystem models. Improved 15 N tracing tools for the analysis of 15 N tracing data in soil-plant systems have been developed that are extensively used by associated partners. DASIM brought together an interdisciplinary network of researchers interested in analytical but also modelling aspects. This includes close collaboration with the FAO/IAEA centre of Nuclear Techniques in Food and Agriculture of the United Nations which resulted in an open access book that describes the methods used in DASIM. The impact of the DASIM research unit on the scientific community is manifold and will most likely have a lasting impact on the understanding of nitrogen cycling in terrestrial ecosystems.

Efficacy assessment in crop protection: a tutorial on the use of Abbott’s formula - Hans-Peter Piepho; Waqas Ahmed Malik; Robert Bischoff; Abbas El-Hasan; Christian Scheer; Jan Erik Sedlmeier; Roland Gerhards; Georg Petschenka; Ralf T. Voegele (Journal of Plant Diseases and Protection, 2024)
In 1925, the American entomologist Walter Sidney Abbott proposed an equation for assessing efficacy, and it is still widely used today for analysing controlled experiments in crop protection and phytomedicine. Typically, this equation is applied to each experimental unit and the efficacy estimates thus obtained are then used in analysis of variance and least squares regression procedures. However, particularly regarding the common assumptions of homogeneity of variance and normality, this approach is often inaccurate. In this tutorial paper, we therefore revisit Abbott’s equation and outline an alternative route to analysis via generalized linear mixed models that can satisfactorily deal with these distributional issues. Nine examples from entomology, weed science and phytopathology, each with a different focus and methodological peculiarity, are used to illustrate the framework.

In-situ N2O and N2 data improved N budget simulation with APSIM and LandscapeDNDC in tropical sugarcane systems - Naoya Takeda; Johannes Friedl; David Rowlings; Edwin Haas; David Kraus; Peter Grace; Clemens Scheer (Agriculture, Ecosystems & Environment, 2024)

Strategies for mitigating N2O and N2 emissions from an intensive sugarcane cropping system - Johannes Friedl; Daniel Warner; Weijin Wang; David W. Rowlings; Peter R. Grace; Clemens Scheer (Nutrient Cycling in Agroecosystems, 2023)
In sugarcane cropping systems, high rates of N fertiliser are typically applied as sub-surface bands creating localised zones of high mineral N concentrations. This in combination with high levels of crop residue (trash) retention and a warm and humid climate creates conditions that are known to promote soil denitrification, resulting in high emissions of the potent greenhouse gas N 2 O. These losses illustrate inefficient use of N fertilisers but total denitrification losses in the form of N 2 and N 2 O remain largely unknown. We used the 15 N gas flux method to investigate the effect of cane trash removal and the use of the nitrification inhibitor 3,4-dimethylpyrazole phosphate (DMPP) on N 2 and N 2 O emissions on a commercial sugarcane farm at Bundaberg, Australia. High gaseous N losses were observed under the standard grower practice where cane trash retention and N fertiliser application (145 kg N ha −1 as urea) resulted in N 2 and N 2 O emissions (36.1 kg N ha −1 ) from the subsurface N fertiliser band, with more than 50% of these losses emitted as N 2 O. Cane trash removal reduced N 2 emission by 34% and N 2 O emission by 51%, but had no effect on the N 2 O/(N 2 + N 2 O) ratio. The use of DMPP lowered N 2 and N 2 O emission by 35% and 98%, respectively, reducing the percentage of these losses (N 2 + N 2 O) emitted as N 2 O to only 4%. We conclude that the use of DMPP is an effective strategy to reduce N losses, minimise N 2 O emissions, while keeping the benefits of cane trash retention in sugarcane cropping systems.

Improving nitrogen use efficiency in irrigated cotton production - Clemens Scheer; David W. Rowlings; Diogenes L. Antille; Massimiliano De Antoni Migliorati; Kathrin Fuchs; Peter R. Grace (Nutrient Cycling in Agroecosystems, 2023)
Irrigated cotton in Australia is mainly grown on heavy textured soils which are prone to waterlogging, resulting in significant losses of nitrogen (N) via denitrification and surface run-off. This study investigated fertiliser nitrogen use efficiency (fNUE) over three seasons on five commercial cotton farms using the 15 N tracer technique. Fertiliser NUE was consistently low across all fertilised treatments, with on average 47% of the applied fertiliser lost and only 17% of the N taken up by the crop derived from fertiliser. There was no significant effect of different N fertiliser products and rates on cotton lint yield. High lint yields (0.9–3.6 Mg ha −1 ) could be achieved even without the application of N fertiliser, demonstrating mineralisation of soil organic N, residual fertiliser, or N returned with crop residues, as key source of N in these cropping systems. Using the nitrification inhibitor DMPP and overhead instead of furrow irrigation showed potential to reduce N fertiliser losses. The results demonstrate that under current on-farm management fNUE is low on irrigated cotton farms in Australia and highlight the need to account for soil N stocks and mineralisation rates when assessing optimized fertiliser rates. There is substantial scope to improve fNUE and reduce N losses without any impact on lint yield, by adjusting N fertiliser application rates, in particular in combination with the use of the nitrification inhibitor DMPP. Using overhead instead of furrow irrigation is a promising approach to improve not only water use efficiency, but also fNUE in irrigated cotton systems.

Combining nitrification inhibitors with a reduced N rate maintains yield and reduces N2O emissions in sweet corn - Jesse Muller; Daniele De Rosa; Johannes Friedl; Massimiliano De Antoni Migliorati; David Rowlings; Peter Grace; Clemens Scheer (Nutrient Cycling in Agroecosystems, 2023)

Interaction between soil and fertiliser nitrogen drives plant nitrogen uptake and nitrous oxide (N2O) emissions in tropical sugarcane systems - Naoya Takeda; Johannes Friedl; Robert Kirkby; David Rowlings; Daniele De Rosa; Clemens Scheer; Peter Grace (Plant and Soil, 2022)
Aims High nitrogen (N) fertiliser inputs in intensive sugarcane systems drive productivity but also significant emissions of nitrous oxide (N 2 O), a potent greenhouse gas. Fertiliser and soil N availability for both plant N uptake and N 2 O emissions across different N rates remain unknown, hindering efficient N management. This study investigated the contribution of fertiliser and soil N and their interaction to plant N uptake and N 2 O emissions in two intensively managed tropical sugarcane systems. Methods High temporal resolution N 2 O measurements were combined with 15 N recoveries across four N fertiliser rates, (100, 150, 200 and 250 kg N ha − 1 ) in soil, plant and N 2 O emissions. Results Cumulative N 2 O emissions ranged from 0.3 to 4.1 kg N ha − 1 , corresponding to emission factors ranging from 0.7 to 2.4%. Native soil N accounted for > 60% of cumulative N 2 O emissions and total plant N uptake. Fertiliser N addition increased N 2 O emissions from native soil N compared to the unfertilised control, highlighting the interaction between fertiliser and soil N, which determined the overall magnitude but also the response of total N 2 O emissions to N rates dependent on the site conditions. Overall fertiliser 15 N loss responded exponentially to N rates with 50% of applied N fertiliser permanently lost even at the recommended N rate. Conclusions The interaction between fertiliser and soil N and its contribution to N uptake and N 2 O emissions demonstrate the importance of integrating soil fertility management with N fertiliser rate recommendations for sugarcane systems to maintain crop productivity and reduce environmental impacts.

Amplitude and frequency of wetting and drying cycles drive N2 and N2O emissions from a subtropical pasture - Johannes Friedl; Evi Deltedesco; Katharina M. Keiblinger; Markus Gorfer; Daniele De Rosa; Clemens Scheer; Peter R. Grace; David W. Rowlings (Biology and Fertility of Soils, 2022)
This study investigated the effects of irrigation frequency on N 2 and N 2 O emissions from an intensively managed pasture in the subtropics. Irrigation volumes were estimated to replace evapotranspiration and were applied either once (low frequency) or split into four applications (high frequency). To test for legacy effects, a large rainfall event was simulated at the end of the experiment. Over 15 days, 7.9 ± 2.7 kg N 2 + N 2 O-N ha −1 was emitted on average regardless of irrigation frequency, with N 2 O accounting for 25% of overall N 2 + N 2 O. Repeated, small amounts of irrigation produced an equal amount of N 2 + N 2 O losses as a single, large irrigation event. The increase in N 2 O emissions after the large rainfall event was smaller in the high-frequency treatment, shifting the N 2 O/(N 2 O + N 2 ) ratio towards N 2 , indicating a treatment legacy effect. Cumulative losses of N 2 O and N 2 did not differ between treatments, but higher CO 2 emissions were observed in the high-frequency treatment. Our results suggest that the increase in microbial activity and related O 2 consumption in response to small and repeated wetting events can offset the effects of increased soil gas diffusivity on denitrification, explaining the lack of treatment effect on cumulative N 2 O and N 2 emissions and the abundance of N cycling marker genes. The observed legacy effect may be linked to increased mineralisation and subsequent increased dissolved organic carbon availability, suggesting that increased irrigation frequency can reduce the environmental impact (N 2 O), but not overall magnitude of N 2 O and N 2 emissions from intensively managed pastures.

Evolution of DNA Methylation Across Ecdysozoa - Jan Engelhardt; Oliver Scheer; Peter F. Stadler; Sonja J. Prohaska (Journal of Molecular Evolution, 2022)
DNA methylation is a crucial, abundant mechanism of gene regulation in vertebrates. It is less prevalent in many other metazoan organisms and completely absent in some key model species, such as Drosophila melanogaster and Caenorhabditis elegans . We report here a comprehensive study of the presence and absence of DNA methyltransferases (DNMTs) in 138 Ecdysozoa, covering Arthropoda, Nematoda, Priapulida, Onychophora, and Tardigrada. Three of these phyla have not been investigated for the presence of DNA methylation before. We observe that the loss of individual DNMTs independently occurred multiple times across ecdysozoan phyla. We computationally predict the presence of DNA methylation based on CpG rates in coding sequences using an implementation of Gaussian Mixture Modeling, . Integrating both analysis we predict two previously unknown losses of DNA methylation in Ecdysozoa, one within Chelicerata (Mesostigmata) and one in Tardigrada. In the early-branching Ecdysozoa Priapulus caudatus , we predict the presence of a full set of DNMTs and the presence of DNA methylation. We are therefore showing a very diverse and independent evolution of DNA methylation in different ecdysozoan phyla spanning a phylogenetic range of more than 700 million years.

Important constraints on soil organic carbon formation efficiency in subtropical and tropical grasslands - Elaine Mitchell; Clemens Scheer; David Rowlings; Francesca Cotrufo; Richard T. Conant; Peter Grace (Global Change Biology, 2021)
More than 10% of Australia's 49 M ha of grassland is considered degraded, prompting widespread interest in the management of these ecosystems to increase soil carbon (C) sequestration—with an emphasis on long‐lived C storage. We know that management practices that increase plant biomass also increase C inputs to the soil, but we lack a quantitative understanding of the fate of soil C inputs into different soil organic carbon (SOC) fractions that have fundamentally different formation pathways and persistence in the soil. Our understanding of the factors that constrain SOC formation in these fractions is also limited, particularly within tropical climates. We used isotopically labelled residue ( 13 C) to determine the fate of residue C inputs into short‐lived particulate organic matter (POM) and more persistent mineral‐associated organic matter (MAOM) across a broad climatic gradient (ΔMAT 10°C) with varying soil properties. Climate was the primary driver of aboveground residue mass loss which corresponded to higher residue‐derived POM formation. In contrast, MAOM formation efficiency was constrained by soil properties. The differential controls on POM and MAOM formation highlight that a targeted approach to grassland restoration is required; we must identify priority regions for improved grazing management in soils that have a relatively high silt+clay content and cation exchange capacity, with a low C saturation in the silt+clay fraction to deliver long‐term SOC sequestration.

No sugar yield gains but larger fertiliser 15N loss with increasing N rates in an intensive sugarcane system - Naoya Takeda; Johannes Friedl; David Rowlings; Daniele De Rosa; Clemens Scheer; Peter Grace (Nutrient Cycling in Agroecosystems, 2021)

Combined effect of nitrogen fertiliser and leaf litter carbon drive nitrous oxide emissions in tropical soils - Hemant Raj Pandeya; Johannes Friedl; Daniele De Rosa; Constancio Tony Asis; Joanne Tilbrook; Clemens Scheer; Mila Bristow; Peter R. Grace; David W. Rowlings (Nutrient Cycling in Agroecosystems, 2020)

Field-scale management and environmental drivers of N2O emissions from pasture-based dairy systems - Daniele De Rosa; David W. Rowlings; Bill Fulkerson; Clemens Scheer; Johannes Friedl; Martin Labadz; Peter R. Grace (Nutrient Cycling in Agroecosystems, 2020)

Nitrogen use efficiency of 15N urea applied to wheat based on fertiliser timing and use of inhibitors - Ashley J. Wallace; Roger D. Armstrong; Peter R. Grace; Clemens Scheer; Debra L. Partington (Nutrient Cycling in Agroecosystems, 2020)
Improving fertiliser nitrogen (N) use efficiency is essential to increase productivity and avoid environmental damage. Using a 15 N mass balance approach, we investigated the effects of five N fertiliser management strategies to test the hypothesis that increasing uptake of applied N by wheat improves productivity and reduces loss of N in a semi-arid environment. Three experiments were conducted between 2012 and 2014. Treatments included urea application (50 kg N/ha) at sowing with and without nitrification inhibitor (3,4-dimethylpyrazole phosphate, DMPP) and surface broadcast with and without urease inhibitor ( n -butyl thiophosphoric triamide, NBPT) at the end of tillering plus an unfertilised control. It was found that deferring fertiliser application until the end of tillering decreased losses of fertiliser N (35–52%) through increasing uptake by the crop and or recovery in the soil at harvest, while maintaining yield except when rainfall following application was low. In this case, deferring application reduced fertiliser uptake (− 71%) and grain yield (− 18%) and increased recovery of N in the soil (+ 121%). Use of DMPP or NBPT reduced N loss where seasonal conditions were conducive to denitrification during winter (DMPP) and volatilisation or denitrification later in the season (NBPT). Their effect on grain yield was less significant; DMPP increased yield (+ 3–31%) in all years and NBPT increased yield (+ 7–11%) in 2 of 3 years compared to unamended urea. The majority of crop N uptake was supplied from soil reserves and as a result, crop recovery of applied N was not strongly related to grain yield response.

Effect of urbanization on soil methane and nitrous oxide fluxes in subtropical Australia - Lona van Delden; David W. Rowlings; Clemens Scheer; Daniele De Rosa; Peter R. Grace (Global Change Biology, 2018)
Increasing population densities and urban sprawl are causing rapid land use change from natural and agricultural ecosystems into smaller, urban residential properties. However, there is still great uncertainty about the effect that urbanization will have on biogeochemical C and N cycles and associated greenhouse gas (GHG) budgets. We aimed to evaluate how typical urbanization related land use change in subtropical Australia affects soil GHG exchange (N 2 O and CH 4 ) and the associated global warming potential (GWP). Fluxes were measured from three land uses: native forest, a long‐term pasture, and a turf grass lawn continuously over two years using a high‐resolution automated chamber system. The fertilized turf grass had the highest N 2 O emissions, dominated by high fluxes >100 g N 2 O‐N day −1 immediately following establishment though decreased to just 0.6 kg N 2 O‐N ha −1 in the second year. Only minor fluxes occurred in the forest and pasture, with the high aeration of the sandy topsoil limiting N 2 O emissions while promoting substantial CH 4 uptake. Native forest was consistently the strongest CH 4 sink (−2.9 kg CH 4 ‐C ha −1 year −1 ), while the pasture became a short‐term CH 4 source after heavy rainfall when the soil reached saturation. On a two‐year average, land use change from native forest to turf grass increased the non‐CO 2 GWP from a net annual GHG sink of −83 CO 2 ‐e ha –1 year −1 to a source of 245 kg CO 2 ‐e ha –1 year −1 . This study highlights that urbanization can substantially alter soil GHG exchange by altering plant soil water use and by increasing bulk density and inorganic N availability. However, on well‐drained subtropical soils, the impact of urbanization on inter‐annual non‐CO 2 GWP of turf grass was low compared to urbanized ecosystems in temperate climates.

Fertiliser timing and use of inhibitors to reduce N2O emissions of rainfed wheat in a semi-arid environment - Ashley J. Wallace; Roger D. Armstrong; Robert H. Harris; Oxana N. Belyaeva; Peter R. Grace; Debra L. Partington; Clemens Scheer (Nutrient Cycling in Agroecosystems, 2018)

Erratum to: Effect of organic and mineral N fertilizers on N2Oemissions from an intensive vegetable rotation - Daniele De Rosa; David W. Rowlings; Johannes Biala; Clemens Scheer; Bruno Basso; James McGree; Peter R. Grace (Biology and Fertility of Soils, 2016)

Effect of organic and mineral N fertilizers on N2O emissions from an intensive vegetable rotation - Daniele De Rosa; David W. Rowlings; Johannes Biala; Clemens Scheer; Bruno Basso; James McGree; Peter R. Grace (Biology and Fertility of Soils, 2016)

Establishing turf grass increases soil greenhouse gas emissions in peri-urban environments - Lona van Delden; Eloise Larsen; David Rowlings; Clemens Scheer; Peter Grace (Urban Ecosystems, 2016)

Rice husk biochar and crop residue amendment in subtropical cropping soils: effect on biomass production, nitrogen use efficiency and greenhouse gas emissions - Dai H. Nguyen; Clemens Scheer; David W. Rowlings; Peter R. Grace (Biology and Fertility of Soils, 2016)

Cerebellar Hypoplasia and Dysmorphia in Neurofibromatosis Type 1 - Sandra P. Toelle; Andrea Poretti; Peter Weber; Tatjana Seute; Jacoline E. C. Bromberg; Ianina Scheer; Eugen Boltshauser (The Cerebellum, 2015)

Assessing agronomic and environmental implications of different N fertilisation strategies in subtropical grain cropping systems on Oxisols - Massimiliano De Antoni Migliorati; Mike J. Bell; Peter R. Grace; David W. Rowlings; Clemens Scheer; Alice Strazzabosco (Nutrient Cycling in Agroecosystems, 2014)

Soil N2O and CO2 emissions from cotton in Australia under varying irrigation management - Clemens Scheer; Peter R. Grace; David W. Rowlings; Jose Payero (Nutrient Cycling in Agroecosystems, 2013)

Nitrous oxide emissions from irrigated wheat in Australia: impact of irrigation management - Clemens Scheer; Peter R. Grace; David W. Rowlings; Jose Payero (Plant and Soil, 2012)

Effect of biochar amendment on the soil-atmosphere exchange of greenhouse gases from an intensive subtropical pasture in northern New South Wales, Australia - Clemens Scheer; Peter R. Grace; David W. Rowlings; Stephen Kimber; Lukas Van Zwieten (Plant and Soil, 2011)

Abstracts of the 6th FECS Conference 1998 Lectures - F. Sherwood Rowland; Donald R. Blake; B. R. Larsen; Anne Lindskog; Peter J. Peterson; W. Peter Williams; T. J. Wallington; M. J. Pilling; N. Carslaw; D. J. Creasey; D. E. Heard; P. Jacobs; et al. (Environmental Science and Pollution Research, 1998)